NTT DALAM CAHAYA ANT: STUDI KASUS PERDAGANGAN MANUSIA BERKEDOK PENGIRIMAN TKI DI NTT - Windy Paskawati Soemarno (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2020)
The case of human trafficking in the NTT has become an unresolved case. Most of the cases of human trafficking in NTT are migrant workers. Human trafficking cases are affected by the actors involved in the network of problems. ANT (Actor-Network Theory) is used as a review to describe the various roles of actors in human trafficking networks and is used to find the point of the problem of human trafficking cases in NTT. The results of this study indicate an indication of the involvement of actors of human trafficking groups participating in trafficking networks. And poverty is a major factor in the rise and fall of human trafficking in NTT. And poverty is a major factor in the unstoppable of human trafficking in NTT. The results of this study also led to the solution of economic empowerment as a way out of poverty to end human trafficking cases in NTT.